Proposition of diagnostic tool to provide indicatives about the understanding of biological knowledge and their interrelationships - Ana Maria de Andrade Caldeira; Paloma Rodrigues Siebert; André Luis Corrêa; Fernanda Aparecida Meglhioratti; Fernanda da Rocha Brando; Fúlvia Eloá Maricato; Lourdes Aparecida Della Justina; Mariana Aparecida Bologna Soares de Andrade; Thais Benetti de Oliveira; Thais Gimenez da Silva Augusto (Universidad Distrital Francisco José de Caldas, 2016)
This paper describes the developing and validating steps of a Likert's evaluative scale. The aim is to systematize the answers of Biological Sciences students about to: 1) Understanding or notunderstanding thescientific knowledge; and 2).If there is a relationship amongscientific concepts in order to contemplate a systemic thinking about natural phenomena. The described scale was validated by Cronbach's Alpha tests (α = 0.741), KMO (0.779) and Bartlett (0.000) and a Multivariate Analysis was fulfilled, typePrincipal Component Analysis (PCA). We understood that this kind of instrument allows a large amount of data to be collected and it groups can be compared efficiently, which justified the development of evaluative scale presented here.